Scarcity, entitlements and the economics of water in developing countries - Anand, P. B.; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2007)
P.B. Anand argues that if water supply and sanitation were mainly problems of technology or financial resources, they would have been resolved long ago. While appreciating that technology and finances are important, he ascertains that there are many other factors affecting our ability to intervene and improve the effectiveness of policies. The author explores these factors, raising questions such as 'How is water scarcity defined?', 'Are there patterns that indicate how nations use available freshwater resources?', 'Does water shortage make nations use water more efficiently?', and 'What explains the variation in progress with regard to Millennium Development Goals related to water and sanitation?'.
Introduction -- Investigating water 'scarcity' -- Access to water supply : achieving the Millennium Development Goal -- Sharing water peacefully : understanding transboundary water-resource conflicts -- An analysis of a river dispute : interaction of politics and economics -- Improving access to water : institutions, entitlements and inequality -- Consumer preferences and public policy -- Justice, rights and sustainability : access to water and the capability approach. -- Conclusions and a research agenda.
Includes bibliographical references (p. 273-298) and index.
Keywords: Water resources development -- Economic aspects -- Developing countries; Water-supply -- Economic aspects -- Developing countries; Electronic books